Preparation and study of a conductive nanocomposite applicable for the wall material of tissue-equivalent proportional counters used in radiation protection. (November 2019) - Moslehi, A.; Khoylou, F.; Akhavan, A.
Abstract: In the present work a tissue-equivalent (TE) nanocomposite is prepared by mixing polyamide 6 (PA6), polyethylene (PE) and carbon nanotubes (CNTs) to be a substitution for the expensive and difficult to obtain A-150 plastic as the wall material of tissue-equivalent proportional counters (TEPCs). It is found that 3% of CNTs in the nanocomposite produced 3  × 10 − 6 S cm − 1 electrical conductivity comparable with that of A-150 and the soft tissue. Also, TEM picture shows the electrical network formation in the continuous PA phase and the interface of PA and PE phases. Determination of the density and the weight percentage of elements of this nanocomposite reveal that the obtained values are similar to A-150 and the soft tissue. On the other hand, simulations carried out by Geant4 toolkit show that the fluence of secondary charged particles of the gamma rays or neutrons inside the gas cavity originating from A-150 and the nanocomposite (3% CNT) is similar. In addition, microdosimetric distributions derived from a TEPC with the nanocomposite wall agree well with a TEPC with A-150 wall. Hence, the frequency-mean and dose-mean lineal energies obtained by the two TEPCs are also compatible. A maximum difference 3% is observed between the frequency-mean lineal energies. Also, the dose-mean lineal energies differ up to 10%. Consequently, the dose-equivalent determined by the two above TEPCs is found similar. Finally, it is concluded that the fabricated nanocomposite can be a reliable substitution for A-150 plastic as a wall material of TEPCs in the neutrons and gamma ray measurements. Highlights: A TE nanocomposite was prepared by mixing polyethylene, polyamide and CNT. With 3% CNT, conductivity, atomic composition and density were similar to A-150. The nanocomposite was found a good substitution for A-150 as the wall of TEPCs.